The effects of some prostaglandins on respiration in anaesthetized cats - McQueen, D.S. (1974)
1 Some prostaglandins have been found to be capable of affecting respiration in anaesthetized cats. 2 Prostaglandins E(1), E(2), F(2α), A(1) and A(2) all elicited increases in respiratory frequency when administered to cats anaesthetized with either pentobarbitone or α-chloralose. This effect was abolished by bilateral vagotomy. 3 Prostaglandins of the E and A series, but not prostaglandin F(2α), elicited increases in tidal volume which were accompanied by falls in systemic blood pressure in cats anaesthetized with pentobarbitone. The changes in blood pressure were also obtained in cats anaesthetized with α-chloralose, but not the tidal volume changes. 4 It is unlikely that the prostaglandins influenced respiration by direct actions on arterial chemoreceptors or baroreceptors. 5 Mechanisms by which the prostaglandins may be acting to affect respiration are discussed.